(λ, μ)-anti-fuzzy linear spaces - S.B. Barge; J.D. Yadav (Journal of Hyperstructures, 2023)
In this article, we introduce the notion of a (λ, μ)-anti-fuzzy fields and a (λ, μ)-anti-fuzzy linear spaces over a (λ, μ)-anti-fuzzy fields and obtain some fundamental properties. Furthermore, we propose the direct product of a (λ, μ)-anti-fuzzy linear spaces and employ it to describe some important properties.